Effects of Gundelia dersim Exosome-Like Nanoparticles on Cell Viability in Human Colon and Lung Cancer Cell Lines - Erman, Fazilet; Kaya, Gül; Turkoglu, Semra (My University, 2023)
Exosomes are nano sized (30-100 nm) bioactive vesicles that constitute the smallest subgroup of extracellular vesicles (EVs). They have properties such as transporting genetic materials, maintaining intercellular communication, regulating immunity, and transmitting signals. Although plant-derived nanoparticles, which exhibit a wide range of therapeutic potential, have not been studied as extensively as in mammalian cells, there is an increasing number of research supporting their cross-kingdom effects. This study aims to investigate the cytotoxic effects of exosome-like nanoparticles isolated from the Gundelia dersim plant (GdENs), which is endemic to Turkey, on cell viability in human lung cancer (A549) and human colon cancer (HCT 116) cell lines. The isolated GdENs were imaged through nanoparticle tracking analysis (NTA). Protein analysis was performed with BCA (Bicinchoninic acid). The nanoparticles were applied on A549 and HCT116 cell lines. By conducting a Water-soluble tetrazolium salt-1 (WST-1) assay, the cytotoxic effect on these cell lines was studied. According to our findings, the increasing concentrations of isolated GdENs on, demonstrated cytotoxic effects by reducing cell viability in HCT 116 cell lines at 75, 100 and 250 ?g/mL within 24, 48 and 72 hours. In A549 cell lines, it was determined that nanoparticles exhibited cytotoxic effects at 24 hours in all concentration units, but did not exhibit any cytotoxic effect by increasing cell viability at 72 hours. In conclusion, GdENs are thought to have therapeutic potential as an anticarcinogen if supported by more comprehensive studies.
Keywords: Cancer; Exosome; Gundelia dersim; Cytotoxic effects